2018
DOI: 10.1002/jso.25317
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic melanoma

Abstract: Desmoplastic melanoma (DM) is a rare melanoma variant that has unique biology and pathology compared with conventional melanoma (non-DM). Importantly, DM is classified into pure and mixed histologic subtypes, which have been correlated with outcomes. Management of DM broadly mirrors that of non-DM; however, there are unique considerations for DM that influence treatment approaches. This paper will provide a contemporary overview of this disease and will review the literature regarding the management of DM. K E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 64 publications
(136 reference statements)
1
46
1
4
Order By: Relevance
“…DM is considered an uncommon subtype melanoma with a frequency of 1% to 4% [14]. In our study, we found that DM corresponded to 1.1% of the total types of melanoma reported on the NCDB.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…DM is considered an uncommon subtype melanoma with a frequency of 1% to 4% [14]. In our study, we found that DM corresponded to 1.1% of the total types of melanoma reported on the NCDB.…”
Section: Discussionsupporting
confidence: 51%
“…As a consequence, the resection of the tumor becomes more difficult, increasing the likelihood of wider resections that result in greater disfigurement at the surgical site. Due to the low incidence of the disease, few studies have described the characteristics of DM, and no study compared them with those of common malignant melanoma (CMM) [7][8][9][10][11][12][13][14]. The aim of this study was to perform a comprehensive national analysis of the characteristics and survival rate of DM and to compare them with those of CMM in the US.…”
Section: Introductionmentioning
confidence: 99%
“…In 1971 Conley et al were the first to describe DM as “an invasive spindle cell tumor with extreme desmoplasia.” DM has a predilection for male gender and older age. Often, it is found on chronically sun‐exposed areas, most common in the head and neck . Breslow thickness is usually greater compared to non‐desmoplastic melanoma (non‐DM), which may be partly explained by the difficulty in diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…Often, it is found on chronically sun‐exposed areas, most common in the head and neck . Breslow thickness is usually greater compared to non‐desmoplastic melanoma (non‐DM), which may be partly explained by the difficulty in diagnosis . DM can easily be confused with other benign or malignant lesions, both clinically and histologically .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation